2014 IEEE/RSJ International Conference on Intelligent Robots and Systems 2014
DOI: 10.1109/iros.2014.6942781
|View full text |Cite
|
Sign up to set email alerts
|

Study of reconfigurable suspended cable-driven parallel robots for airplane maintenance

Abstract: This paper discusses the use of large-dimension reconfigurable suspended cable-driven parallel robots (CDPR) to substitute for conventional gantry nacelles that carry workers in an airplane maintenance workshop. The reconfiguration of the CDPR is considered as a multi-objective optimization problem with two performance indices. One criterion is the sum of the cable tensions which is directly related to the power consumption of the CDPR. The other criterion is the normalized upper bound on the infinitesimal dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Superscript d indicates the desired (prescribed) values and e Fx ; e Fy ; and e M are the maximum acceptable distances between mean and the desired values of the wrench vector elements. Inequality constraint (33) ensures the kinematic feasibility of the cable orientations (typically to avoid the collision) and (34) guarantees that optimal tensions are consistent with the force capacity of the agents. Depending on application scenario, different variant of optimization problems can be formulated by selecting various combinations of objective functions.…”
Section: Base Configuration and Cable Tension Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Superscript d indicates the desired (prescribed) values and e Fx ; e Fy ; and e M are the maximum acceptable distances between mean and the desired values of the wrench vector elements. Inequality constraint (33) ensures the kinematic feasibility of the cable orientations (typically to avoid the collision) and (34) guarantees that optimal tensions are consistent with the force capacity of the agents. Depending on application scenario, different variant of optimization problems can be formulated by selecting various combinations of objective functions.…”
Section: Base Configuration and Cable Tension Optimizationmentioning
confidence: 99%
“…Although conventional cable-robots use fixed bases with varying cable lengths [23][24][25][26][27][28], recent studies [29][30][31][32][33][34][35] focus on reconfigurable systems where the cable lay out can be changed through mobility of the bases. The configuration optimization has been considered to improve some performance indices such as dexterity [30], tension factor [32,36], and power consumption and stiffness [34,35]. However, in this work, our main focus is to reduce the uncertainty of the generated wrench at the platform that directly impacts the platform position uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…Barbazza et al [21] proposed a reconfigurable end-effector for industrial operations where cables are reconfigured in each stage to avoid collisions and a planned trajectory to minimize reconfiguration times. Nguyen et al [22] studied a larger reconfigurable robot for transporting personnel in an airplane maintenance shop, taking into consideration the top limit of displacement of the mobile platform and the increase of energy usage due to the tensions on the cables. Pott et al [23] suggested a method to determine the space taken by the cables when the robot is moving, considering that the cable trajectory takes the form of a cone.…”
Section: Introductionmentioning
confidence: 99%
“…Rosati et al [32,36] and Zhou et al [38,39] focused their work on planar RCDPRs. Recently, Nguyen et al [27,26] proposed reconfiguration strategies for large-dimension suspended CDPRs mounted on overhead bridge cranes. Contrary to these antecedent studies, this chapter considers discrete reconfigurations where the locations of the cable exit points are selected from a finite set (grid) of possible values.…”
Section: Introductionmentioning
confidence: 99%